Endgame: The false destruction of the social imaginary - Nina Boy (Finance and Society, 2021)
Vogl's account of contemporary financial truth games suggests that a full understanding of our present condition requires the kind of knowledge produced by fiction and those who study it. But what kind of knowledge is that, and how does it escape the capitalist ontology of information?
Keywords: 300